The practice of smoking cessation counseling in community pharmacy / Elya Noor Seikh Omar - Seikh Omar, Elya Noor (2006)
As a key interface between patients and the health-care community, pharmacists are uniquely positioned to promote smoking cessation. The objectives of this study were to identify the trend of community pharmacists in practicing smoking cessation and the interest of the community pharmacists in receiving specialized training for smoking cessation counseling. A six-page survey, preceded by a cover letter and a self- addressed were sent directly to the community pharmacists in Shah Alam (n=25). All analyses were conducted using Statistical Package for the Social Sciences (version 12.0.1; SPSS, Inc). A total of 25 surveys were collected from the community pharmacies in Shah Alam. Only sixty-four percent (64%) of the pharmacists ever attended any smoking cessation training or workshop. Thirty-six percent (36%) of the pharmacists who haven't attended any smoking cessation training or workshop were interested in attending any of the training or workshop. Eighty percent (80%) of the community pharmacists received patients related to smoking cessation program with average 1.20 ± 0.48 patients per week. More than seventy percent (70%) of the community pharmacists think that the 5 A's Treatment Model is important in order to help patients to quit smoking. Lack of time, patients are not responsive to suggestions and patients usually do not wish to quit were identified as the greatest barrier to counseling patients who smoke. While there are opportunities for pharmacists to increase their involvement in smoking cessation related activities especially counseling, a change in current practices is needed. Pharmacists should begin to routinely document patients' smoking status and encourage smoking cessation at every opportunity that they have.